The Environment in Asia Pacific Harbours - Wolanski, Eric (Springer Netherlands : Imprint: Springer, 2006)
Urbanization has already reached unprecedented levels in the estuarine and coastal zone of the Asia Pacific region where mega-cities and mega-harbours have developed and are still growing. Environmental degradation is significant and growing. The social, economic and environmental problems are pressing and call for science-based solutions. This book details how science can provide solutions so that economic and social developments can be ecologically sustainable. Twelve sites are discussed in detail, integrating physics and biology, and between science and engineering. In turn these are linked to economic and social issues. These sites are Tokyo Bay, the Pearl Estuary, Hong Kong, Shanghai and the Yangtze delta, Klang, Manila Bay, Jakarta Bay, Pearl Harbor, Ho Chi Minh City, Bangkok and the upper Gulf of Thailand, Singapore, and Darwin. This is the shoreline of about 50 million people and the coastal waters of about 500 million people. Sixty prominent scientists and engineers in universities and research centres in all these cities contributed the chapters in this book. These lessons are fundamentally important for the Asia Pacific region, and they will also substantially inform similar analyses of mega-cities, port and harbour management and practices worldwide.